An introduction to Greek mythology - Bellingham, David (Secaucus, N.J. : Chartwell Books, 1989)
Describes the beliefs, gods, buildings and animals worshiped by the ancient Greeks, from Athens to Zeus
"A Quintet book."
Includes index.
Bibliography: p. 124.
Keywords: Mythology, Greek; Classical mythology